PENINGKATAN DISIPLIN GURU DALAM KEHADIRAN MENGAJAR DI KELAS MELALUI KETELADANAN OLEH KEPALA SEKOLAH - Fransiska Name (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
The purpose of this study is to determine the increase in teacher discipline in teaching attendance in the classroom through the example of the principal. The type of research used is school action research (PTS). The research was conducted in two cycles and each cycle consisted of four stages: planning, implementation, observation, and reflection. The subjects in this study were the teachers of SDK Santa Theresia Ende 3 totaling 29 people consisting of 26 female teachers and 3 male teachers. Data collection techniques used are observation, observation, and interviews. The research instrument is an assessment scale, observation sheet/observation, and a questionnaire. An indicator of the success of implementing this action is if 75% of teachers in the learning process are not late in teaching class. The results showed that the principal's example of giving warnings in the form of verbal and written reprimands for teachers who were late for class could improve teacher discipline in teaching attendance in the course. This is indicated by the results of research in cycle 1 that the teacher's lateness in class 10 minutes to 15 minutes in the learning process is still high, namely 13 people or 44.83%, and teacher delays in class more than 15 minutes as many as 10 people or 34.48%. Then decreased to 3 teachers who were late for class 10 minutes to 15 minutes, and no more teachers were late for more than 15 minutes.